Building Block in Digital Tax Administration: Literature Review - Nurhayati Nurhayati; Iskandar Muda; Sambas Ade Kusuma (CV. Ridwan Publisher, 2023)
The success of tax administration can be seen from the high awareness of taxpayers and private parties who are responsive to e-filing programs and tax services. The implementation of digital taxation has a positive and beneficial impact on taxpayers and tax officers in the form of effectiveness such as the availability of e-tax services, in accessing which can be done anytime and anywhere. The implementation of digital taxation has a positive and beneficial impact on taxpayers and tax officers in the form of effectiveness such as the availability of e-tax services, in accessing which can be done anytime and anywhere. This study aims to present a literature review on Building Blocks in Tax Administration. The study focuses on the definition of research questions outlining problems, therefore, research questions are formulated, characteristics of respondents, problems solved, results obtained and constraints detected by implementing Building Blocks in Tax Administration. The results obtained by implementing Building Blocks in Tax Administration are as a form of identifying groups of individuals, companies and governments to increase tax compliance and to reduce tax evasion, create models and be able to design models related to increasing taxpayer compliance in paying taxes.